2013
DOI: 10.1103/physrevd.88.015002
|View full text |Cite
|
Sign up to set email alerts
|

Constraining models with a large scalar multiplet

Abstract: Models in which the Higgs sector is extended by a single electroweak scalar multiplet X can possess an accidental global U(1) symmetry at the renormalizable level if X has isospin T greater or equal to 2. We show that all such U(1)-symmetric models are excluded by the interplay of the cosmological relic density of the lightest (neutral) component of X and its direct detection cross section via Z exchange. The sole exception is the T=2 multiplet, whose lightest member decays on a few-day to few-year timescale v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 50 publications
0
47
0
Order By: Relevance
“…This accidental symmetry cannot be spontaneously broken without generating a phenomenologically unacceptable extra Nambu-Goldstone boson. All such models preserving the U(1) are excluded by dark matter cosmological relic densities and direct-detection cross section via Z exchange [7]. In this paper we are not concerned with dark matter and will thus explicitly break the accidental symmetry with a nonrenormalizable operator as done in [4].…”
Section: Jhep05(2014)150mentioning
confidence: 99%
“…This accidental symmetry cannot be spontaneously broken without generating a phenomenologically unacceptable extra Nambu-Goldstone boson. All such models preserving the U(1) are excluded by dark matter cosmological relic densities and direct-detection cross section via Z exchange [7]. In this paper we are not concerned with dark matter and will thus explicitly break the accidental symmetry with a nonrenormalizable operator as done in [4].…”
Section: Jhep05(2014)150mentioning
confidence: 99%
“…The term proportional to λ 4 is not present in the models with Y = 2T considered in Ref. [19]. This term couples two SM Higgs fields Φ (not Φ * ) to two Z * fields, with each pair arranged in an isospin-triplet configuration with total hypercharge ±2.…”
Section: The Modelsmentioning
confidence: 99%
“…We studied these models in Ref. [19] and showed that all except the n = 5 model are excluded by dark matter direct detection experiments assuming a standard thermal history of the universe. The model with n = 5 avoids exclusion from this constraint because its lightest member can decay via a dimension-5 Planck-suppressed operator with a lifetime short compared to the age of the universe.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that there could be an infinite number of models satisfying the above generic features. But when considering constraints from perturbative unitarity 2 [63,64], we will concentrate on SU(2) L scalar multiplet no larger than quintuplet in this paper. Meanwhile, the number of candidate models could be significantly reduced when we only consider the models with non-tuning VEVs for additional scalars S 1,2 [18].…”
Section: Jhep04(2017)166mentioning
confidence: 99%